The car - Parker, Steve (New York : Gloucester Press, 1993)
Text and photographs examine the development of the modern car in all its aspects and explores its social impact.
Includes index and glossary.
Booklist
Library Talk
8.2
5-8
Keywords: Automobiles -- History -- Juvenile literature; Automobiles -- Social aspects -- Juvenile literature; Automobiles -- Design and construction -- Juvenile literature; Automobiles -- History; Automobiles -- Social aspects; Automobiles -- Design and construction; Automobiles -- History; Automobiles -- Social aspects; Automobiles -- Design and construction